2017
DOI: 10.1002/chem.201701316
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Bambusuril Anion Affinity in Water

Abstract: Neutral and negatively charged anion receptors functioning in pure water are rare in supramolecular chemistry. Moreover, studies on adjusting the affinity of such receptors toward anions in water are absent from the literature. Two new bambusurils, 1 a and 2 a, were prepared to demonstrate that the affinity of bambusurils towards anions can be altered by the length of carboxyalkyl groups attached to the macrocycles. The stability of the bambusuril complexes was further controlled by the pH value. The crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(104 citation statements)
references
References 29 publications
8
96
0
Order By: Relevance
“…We further concluded that the chaotropic effect presents a generic driving force that accounts for the intrinsic affinity of chaotropic ions, prominently anions, for neutral organic or inorganic matter, including concave macrocyclic binding sites, lipid bilayers, membranes, and polymers 11, 12, 13, 16, 17, 18, 22, 24, 28, 40, 43, 44, 45, 46, 47, 48. It should be noted that indications for the affinity of anions to hydrophobic binding sites existed early in the literature81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103 but were in part attributed to a putative hydrophobic (or lipophilic) property of large anions, implying the hydrophobic effect as driving force.…”
Section: Thermochemical Hydration Characteristicsmentioning
confidence: 85%
See 1 more Smart Citation
“…We further concluded that the chaotropic effect presents a generic driving force that accounts for the intrinsic affinity of chaotropic ions, prominently anions, for neutral organic or inorganic matter, including concave macrocyclic binding sites, lipid bilayers, membranes, and polymers 11, 12, 13, 16, 17, 18, 22, 24, 28, 40, 43, 44, 45, 46, 47, 48. It should be noted that indications for the affinity of anions to hydrophobic binding sites existed early in the literature81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103 but were in part attributed to a putative hydrophobic (or lipophilic) property of large anions, implying the hydrophobic effect as driving force.…”
Section: Thermochemical Hydration Characteristicsmentioning
confidence: 85%
“…The chaotropic effect extends to molecular recognition events with macrocyclic hosts,10, 12, 21, 22, 23, 24, 25, 26, 27 biologically relevant interactions with proteins and peptides,13, 28, 29, 30, 31, 32 association to small organic molecules,10, 33 binding to membranes,17, 34, 35, 36, 37, 38 polymers,39 as well as colloids,15, 18, 40 and it manifests itself in solid‐state structures between superchaotropic ions and organic components 10, 12, 26, 41, 42. The terms “chaotropic effect” and “superchaotropic ions” have been readily absorbed by the chemical literature in different contexts 11, 12, 13, 15, 16, 17, 18, 22, 24, 28, 40, 41, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54. This relevance in several areas of chemistry reveals the chaotropic effect as a generic driving force, orthogonal to the hydrophobic effect.…”
Section: Introductionmentioning
confidence: 99%
“…In this form, the macrocycle is soluble in organic solvents. [30] Different types of templates for bambus [6]uril synthesis have been tested including halides, BF 4 À , ClO 4 À , and others. [29] A recently published synthesis of water soluble ((CH 2 ) 3 COOH)BU [6] and ((CH 2 ) 5 COOH) BU [6] macrocycles describes conditions compatible with polar groups on macrocycle without the need for prior esterification of monomers.…”
Section: Macrocyclization Reactionmentioning
confidence: 99%
“…The size of the BU cavity can be controlled by the presence of a template. [7] More specifically, BU [6] emerges mainly due to the presence of anions that are recognized by the six glycoluril subunits through directional CH···anion hydrogen bonds. It was found that the strength of these interactions depends on several criteria, such as the type of solvent, solvation, or size and shape of the anion. )…”
Section: Synthesis Of Bambus[6]urils 7abmentioning
confidence: 99%
“…We recently demonstrated that BU[n]s are able to bind various anions in water very efficiently. [2,7] The water solubility of these BU[n]s was achieved by decorating their portals with substituents bearing carboxylate functions. Such substitutions make bambusuril portals negatively charged, which complicates the en-trance of anions.…”
Section: Introductionmentioning
confidence: 99%